Market competitive strategy, government ownership and audit firm choice: evidence from China - Zheng Wei; Mohd Mohid Rahmat (Penerbit Universiti Kebangsaan Malaysia, 2023)
Many serious audit failures of listed companies, mainly in China, have spotlighted the suitability of the appointed audit firm with the companies’ market competitive strategy. This study argues that the adopted market competitive strategy, either offensive or defensive, may influence audit firm choice, but the associations remain unclear. This study investigates the association between market competitive strategy and audit firm choice among Chinese listed companies, with government ownership as a moderator. A logistic multivariate regression analysis was conducted by using 9,590 year-observations of Chinese-listed companies during the period of 2018–2021. Results show that companies with aggressive offensive strategies tend to appoint larger audit firms, whereas companies with aggressive defensive strategies favour smaller audit firms. No evidence shows that government-owned companies influence audit firm choice, but government ownership moderates the relationship between market competitive strategies and audit firm choice. The findings are useful for listed companies to select the best audit quality that fits with the adopted market competitive strategy and provide references for regulators to assess and promote the healthy development of China’s audit market. This work is a pioneer in providing associations among market competitive strategy, government ownership and audit firm choice